Usable Agricultural Area of Farms and their Material and Energy Expenditure Efficiency (Agricultural Engineering, 2020)
The paper analyzes the efficiency of material and energy expenditure in 679 farms with agricultural production as the main source of income for the years 2013-2015. Six groups of farms were identified according to usable agricultural area (UAA). The aim of the work was to determine the impact of UAA of farms on their material and energy expenditure efficiency. It was found that the area of UAA determines the farms’ material and energy expenditure efficiency. It was observed that small farms with UAA of 5 to 10 ha are characterized by the highest material and energy expenditure efficiency. It was proven that the material and energy expenditure efficiency in “Small” farms with UAA (<= 5ha) and “Very large”, with UAA (> 50ha) differs significantly from the efficiency determined for other farm groups. Material and energy expenditures were used the least efficiently in the farms with the smallest UAA.